On L(2,1)-labeling of the Cartesian product of a cycle and a path - Jha, Pranava K.; Sunder, Vivek; Sundaram, Karthik; Sood, Puneet; Narayanan, Ashok (2000)
Sharp bounds are presented for the lambda-number of the Cartesian product of a cycle and a path, and of the Cartesian product of two cycles.